Floridians' Perceptions of GMOs: GMOs and Florida Citrus - Nicole M. W. Dodds; Laura M. Gorham; Joy N. Rumble (EDIS)
This is a minor revision of an EDIS publication focusing on Floridians’ intent to purchase GMO citrus. It is intended to help Extension faculty understand public perceptions regarding the use of genetic engineering to combat citrus greening. Extension faculty can use this understanding of public perceptions as they develop and deliver programming for clientele. This 4-page fact sheet was written by Nicole M. W. Dodds, Laura M. Gorham, and Joy N. Rumble, and published by the Department of Agricultural Education and Communication, November 2017.